1990
DOI: 10.1093/bja/64.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucose Concentration on the Intrathecal Spread of 0.5% Bupivacaine

Abstract: We have studied the effects of intrathecal injection of 0.5% bupivacaine in solutions containing different concentrations of glucose (0.33%, 0.83% and 8%) in three groups of 10 patients. The mean maximum extent of sensory block was significantly higher with 8% glucose (T3.6) than with 0.83% glucose (T7.2) or 0.33% glucose (T9.5). Administration of solutions containing 0.33% glucose produced a greater variability in upper level of sensory block (11 dermatomes) than the two other concentrations (six dermatomes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…2-~ Bannister et al demonstrated an increase in the average level of sensory block, from T 9 to T z as a result of increasing the local anaesthetic density by 0.0027 g.ml -I, in the isobaric range. 4 Baricity of an intrathecal agent is defined as the relative density of agent to that of cerebral spinal fluid (CSF) at specified temperatures, s The density of human CSF has been determined by a number of authors, allowing local anaesthetic density to be defined as hypobaric, isobaric or hyperbaric relative to CSF density, s-7 Using mechanical oscillation resonance frequency techniques, Richardson et al, have determined the density of human CSF to be 1.00064 • 0.00012 g.ml -I for men and 1.00049 • 0.00004 g ml -I for premenopausal nonpregnant women, with an upper limit of hypobaricity of 1.00016-1.00037 g.m1-1 at 37~ 7 Relative to CSF, some local anaesthetics, previously designated to be isobaric, are actually slightly hypobaric at 37~ s-l~ Addition of opioids to intrathecal local anaesthetics has become a popular method of enhancing analgesia associated with spinal anaesthesia. 1~ Opioid densities are lower than hyperbaric and, in some cases, isobaric local anaesthetics) ~ While the effect of adding opioids to isobaric local anaesthetics has been examined, I~ changes in the density of hyperbaric or isobaric local anaesthetics associated with opioid addition have not been defined ha terms of the predictability of the final anaesthetic/opioid mixture density.…”
mentioning
confidence: 99%
“…2-~ Bannister et al demonstrated an increase in the average level of sensory block, from T 9 to T z as a result of increasing the local anaesthetic density by 0.0027 g.ml -I, in the isobaric range. 4 Baricity of an intrathecal agent is defined as the relative density of agent to that of cerebral spinal fluid (CSF) at specified temperatures, s The density of human CSF has been determined by a number of authors, allowing local anaesthetic density to be defined as hypobaric, isobaric or hyperbaric relative to CSF density, s-7 Using mechanical oscillation resonance frequency techniques, Richardson et al, have determined the density of human CSF to be 1.00064 • 0.00012 g.ml -I for men and 1.00049 • 0.00004 g ml -I for premenopausal nonpregnant women, with an upper limit of hypobaricity of 1.00016-1.00037 g.m1-1 at 37~ 7 Relative to CSF, some local anaesthetics, previously designated to be isobaric, are actually slightly hypobaric at 37~ s-l~ Addition of opioids to intrathecal local anaesthetics has become a popular method of enhancing analgesia associated with spinal anaesthesia. 1~ Opioid densities are lower than hyperbaric and, in some cases, isobaric local anaesthetics) ~ While the effect of adding opioids to isobaric local anaesthetics has been examined, I~ changes in the density of hyperbaric or isobaric local anaesthetics associated with opioid addition have not been defined ha terms of the predictability of the final anaesthetic/opioid mixture density.…”
mentioning
confidence: 99%
“…33 The discharge time of patients in the plain ropivacaine group was in accordance with other studies comparing plain ropivacaine with hyperbaric ropivacaine at doses up to 15 mg. [34][35][36][37] Nevertheless, it is difficult to compare sensory or motor recovery due to a number of differences between the various studies, including study design, injection techniques (median, paramedian, slow injection, needle orifice facing up or toward the patient's head/toe), 11,33 needles (25-27G), 33,38 location of lumbar space (L1/L2 -L4/L5), 38,39 patient management after injection (immediate turning to supine position or remaining in the lateral position for a longer period), [38][39][40] and motor scales (Bromage, modified Bromage scale). 33,35,41,42 The mean (SD) time from spinal anesthesia to discharge home was 346 (73) min in the ropivacaine group. This time is in accordance with the mean (SD) values found by Casati et al [322 (57) min] in patients scheduled for inguinal herniorrhaphy under unilateral spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Nevertheless, recent studies using lidocaine solutions injected in the lateral decubitus position have produced controversial results. Toft et al compared 80 mg isobaric lidocaine solution (2%, 4 ml) with80 mg hyperbaric lidocaine solution (5%,1.3ml) and found no difference in the cephalic spread of the sensory or motor block.…”
Section: Discussionmentioning
confidence: 99%
“…He found that concentration, volume, and baricity had no effect on the cephalad spread of the block. Other studies using bupivacaine [1][2][3][4] found that cephalad spread was greater by an average of two dermatomes when a HB formulation was used. Unlike Bengtsson's experiment, the subjects were injected in the lateral decubitus position and not the sitting position.…”
Section: Discussionmentioning
confidence: 99%